GAMBARAN KEMATANGAN KARIER SISWA SMA NEGERI 1 CIBEBER - Septiani Septiani; Siti Fatimah; Ecep Supriatna (IKIP Siliwangi, 2021)
This research aims to describe the level of career maturity of learners at SMA Negeri 1 Cibeber high school. The approach to this research is through quantitative approaches through descriptive methods. The data collection in this study used career maturity instruments based on the theory of Sciarra D. T in the form of likert-scale questionnaires adapted from previous research. Sampling techniques in this study used proportional random sampling technique through the slovin formula, so that it could be sampled as many as 106 learners. The results showed that the level of career maturity of learners in SMA Negeri 1 Cibeber high school in the low category was as many as 17 learners with a percentage of 16%, in the moderate category as many as 69 learners with a percentage of 65%, and in the high category, as many as 20 learners with a percentage of 19%. Meanwhile, when viewed by gender, male learners in the low category had as many as 10 learners with a percentage of 9%, in the moderate category, as many as 31 learners with a percentage of 29%, and in the high categories, as many as 6 learners with a percentage of 6%. While female learners in the low category as many as 7 learners with a percentage of 7%, in the moderate category as many as 38 learners with a percentage of 36%, and in the high category as many as 14 learners with a percentage of 13%. Based on the overall data, students of SMA Negeri 1 Cibeber high school have a picture of career maturity in the moderate category, meaning that the career maturity of learners is at a fairly good stage. Learners are able to plan, explore, and are able to make career decisions. Keywords: : Career Maturity, High School Students